Why do we Moot? Exploring the Role of Mooting in Legal Education - Andrew Lynch (Legal Education Review)
One of the most specialised pieces of assessment featured in a law degree is the moot. Most Law Schools have a mooting component in some form and at some level, yet given the sparseness of the literature on this topic, it seems that the presence and use of mooting is rarely called into question. The only apparent reasons for the existence of mooting programmes are tradition and the correlation to the realities of professional practice. But is this enough? The overall purpose of this article is to provide valid educational and practical justifications for the exercise of mooting. This process begins by defining the essential characteristics of mooting, as it has existed over the centuries. This discussion will be given contemporary relevance by an examination of how three Queensland Law Schools currently feature moots in their undergraduate curriculum. The three theoretical bases for mooting as a means of learning, which the paper explores are constructivism, experiential learning and problem-based learning. As such, mooting has a clear role to play in a law curriculum informed by such educational perspectives. There is also a general discussion on the place of moots in the student approaches to learning (SAL) framework. Additionally, the paper seeks to reveal student reactions to mooting through qualitative research. It is not particularly beneficial to place moots in a theoretical context if there is little understanding of their practical effect. The data gathered from the focus group interviews conducted for this study supports many of the propositions made in the earlier section of the paper, where moots are viewed from the perspective of educational theory. The final part of the paper seeks to take all of the above and make a statement about the value of moots as a form of assessment in the law curriculum. The purposes of assessment are discussed in conjunction with the theoretical views of mooting examined earlier in the paper, as well as the practical outcomes of mooting identified in the group interviews. The conclusion is reached that there are excellent practical and theoretical justifications for moots and by appreciating these reasons, law teachers can begin to better understand the strengths and benefits of this assessment tool.